The Social Marketing Strategy of Solo Bersih Community in Creating Public Awareness of Managing Waste - Fathika Azzahra; Agus Triyono (Jogjakarta Communication Conference (JCC), 2024)
Environmental change and lack of waste management efforts now become crucial issues that often go unnoticed and can be fatal to society. The existence of Solo Bersih Community (KSB) is a non-profit organization that emerged with a movement to create concern for the environment and waste in Solo City (Surakarta) to bring a change in people's behavior for the better. This study aims to determine the application of social marketing by KSB. This research is also supported by social marketing theory, conducted qualitatively descriptive with case study method. The main data obtained from the study were sourced from interviews and observations. A literature study was conducted to find supporting data. This research resulted in findings of four important points that become a benchmark for the success of KSB’s social marketing, including the implementation of persuasive activities in campaigning public awareness, applying four levels of communication approach to target adopters in delivering campaign messages and building strong community representatives, the role of stakeholders in collaborating on program implementation, and sufficient access to information media as a transmission channel for delivering messages to the public. KSB also optimizes four communication strategies, namely redundancy, canalizing, informative, and educative. It can be concluded that social marketing in a community is the key to changing people's behavior if it can be applied with effective communication strategies.